Localisation of chromogranin A and B, met-enkephalin-arg6-gly7-leu8 and PGP9.5-like immunoreactivity in the developing and adult rat adrenal medulla and extra-adrenal chromaffin tissue. - Kent, C (1989)
The localisation of chromogranins A and B, met-enkephalin-arg6-gly7-leu8 (met-enk 8) and protein gene product 9.5 (PGP 9.5) in the adrenal medulla and extra-adrenal chromaffin tissue has been studied in the developing rat by immunogold-silver staining. In the adult rat adrenal the cytoplasm of all medullary chromaffin cells showed a positive response with chromogranin A and B; in each case occasional groups of cells with a low reactivity that may have been NA cells were seen. Chromogranin A was first detected in adrenal medullary and extra-adrenal chromaffin cells at 18 days of gestation whilst chromogranin B was not detected in animals younger than 7 days. In 15 days old animals the adrenal medullary response to A and B was of the same intensity as that seen in the adult. Less than 1% of adult medullary chromaffin cells were responsive to met-enk 8 staining and medullary cells were unreactive in the fetus, with only extra-adrenal chromaffin tissue responding prenatally. During the first postnatal week immunoreactive cells appeared in the adrenal medulla in considerably greater proportions than in the adult gland. In contrast, positively stained nerve terminals associated with chromaffin cells and abundant in the adult adrenal were not detected during the first week of life. Immunoreactive nerve terminals were first seen early in the second week of life at a time when positive chromaffin cells were becoming less common. PGP 9.5 was located in all chromaffin cells of the adult adrenal and was readily detected in chromaffin cells in the adrenal and in extra-adrenal locations of the earliest stage examined (E16). Our findings suggest that the ontogenesis of the chromogranin-like immunostaining reflects the maturation of chromaffin granules and the PGP 9.5 immunostaining detected a protein common to cells of neuronal origin and expressed at an early stage of differentiation. The reciprocal relationship between the presence of enkephalins in chromaffin cells and in their presynaptic terminals merits further investigation.